2021
DOI: 10.1038/s41531-021-00205-7
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal interhemispheric resting state functional connectivity in Parkinson’s disease patients with impulse control disorders

Abstract: Impulse control disorders (ICD) in Parkinson’s disease (PD) might be attributed to misestimate of rewards or the failure to curb inappropriate choices. The mechanisms underlying ICD were reported to involve the lateralization of monoamine network. Our objective was to probe the significant role of lateralization in the pathogenesis of ICD. Twenty-one PD patients with ICD (PD-ICD), thirty-three without ICD (PD-no ICD), and thirty-seven healthy controls (HCs) were recruited and performed T1-weighted, diffusion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Resting-state functional magnetic resonance imaging (rs-fMRI) has emerged as a powerful tool that offers a potential means of identifying novel, sensitive biomarker signatures associated with specific brain disorders (3)(4)(5)(6). A growing body of evidence suggests that abnormal changes in patients with SCH are primarily found in the striatum (7), temporal lobe (8), default-mode network (DMN) (9), and frontoparietal network (10), although the specific nature of these changes has varied across studies, with some reporting functional signal increases (11-13), decreases (14), or both (15).…”
Section: Introductionmentioning
confidence: 99%
“…Resting-state functional magnetic resonance imaging (rs-fMRI) has emerged as a powerful tool that offers a potential means of identifying novel, sensitive biomarker signatures associated with specific brain disorders (3)(4)(5)(6). A growing body of evidence suggests that abnormal changes in patients with SCH are primarily found in the striatum (7), temporal lobe (8), default-mode network (DMN) (9), and frontoparietal network (10), although the specific nature of these changes has varied across studies, with some reporting functional signal increases (11-13), decreases (14), or both (15).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 illustrated the initial search results and selection process. The study included 20 studies (Cilia et al, 2008 ; Frosini et al, 2010 ; Rao et al, 2010 ; van Eimeren et al, 2010 ; Voon et al, 2011 ; Ray et al, 2012 ; Cerasa et al, 2014 ; Lee et al, 2014 ; Biundo et al, 2015 ; Yoo et al, 2015 ; Premi et al, 2016 ; Tessitore et al, 2016 , 2017a , b ; Markovic et al, 2017 ; Filip et al, 2018 ; Imperiale et al, 2018 ; Verger et al, 2018 ; Esteban-Peñalba et al, 2021 ; Gan et al, 2021 ) (including 341 PD-ICD and 437 PD-no ICD).…”
Section: Resultsmentioning
confidence: 99%
“…N = 1 study (Rao et al, 2010 ) (including 9 PD-ICD and 9 PD-no ICD patients) showed significantly reduced regional cerebral blood flow (rCBF) in the right ventral striatum in PD-ICD, compared to PD-no ICD patients. N = 4 studies (Tessitore et al, 2017a , b ; Imperiale et al, 2018 ; Gan et al, 2021 ) (including 86 PD-ICD and 113 PD-no ICD patients) compared resting-state brain activation between PD-ICD and PD-no ICD patients. The ALE study showed reduced resting-state brain activation in the right IFG, the right PCG, the left insula and the right transverse temporal gyrus (TTG) in PD-ICD, compared to PD-no ICD patients ( Figure 3A and Supplementary table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Strong and weak homotopic RSFC were interpreted as a tendency to coordinate processing or independent processing in allelic brain regions, respectively (Baldo et al, 2001). In the past, many functional imaging studies have discovered impaired interhemispheric coordination among PD patients (Hu et al, 2015;Zhu et al, 2016;Li et al, 2018;Gan et al, 2021). The focus of this study was to explore changes in functional coordination of homotopic brain regions post-DBS.…”
Section: Discussionmentioning
confidence: 99%